Legal Protection of Hospital Patients in the Corona Virus Pandemic Period - Yoga Khirari Haggai; Erikson Aritonang; Pandini Riata M (Journal La Sociale, 2020)
This study aims to explain the legal protection for patients during the Covid-19 pandemic and the protection mechanism for patients as consumers. This research used doctrinal research. Basically, health development involves all aspects of life, physical, mental and socio-economic. In the growth of health development so far, there has been a change in orientation, both value ​​and thought, especially regarding effort to solve problem in the health sector which are influenced by politic, economic, socio-cultural, defence and security as well as science and technology. The change of orientation will affect the implementation process of health development. Health development, which is basically the responsibility of the state, becomes very important because the private sector also participates in creating a product in the health sector. This society is generally referred to as consumer. Indonesia and all over the world are currently in a pandemic of the Covid-19 virus, where the virus is spreading so fast. Not yet found anti-virus against this virus, the only way is that everyone is obliged to maintain immunity in the body. But it is very unfair for other patients, currently the focus of medical personnel and hospital is to deal with the Covid-19 outbreak, so that the rights of other patients cannot be fulfilled.